A new high performance variable step size perturb-and-observe MPPT algorithm for photovoltaic system - Khadidja Saidi; Mountassar Maamoun; M’hamed Bounekhla (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The optimization of energy in a photovoltaic conversion chain remains a topic of study. The maximum power point tracking (MPPT) is considered the most appropriate solution to ensure the extraction of the maximum power which a photovoltaic generator can provide. Perturb and observe (P&O) algorithm is the well-known MPPT tracker; it shows an important and decisive role in the development of photovoltaic (PV) systems. In This article we introduce a new improved adjustable step size P&O (imVS_PO) MPPT method.The performances of the new algorithm are compared to the conventional P&O MPPT techniques and to the existing adjustable step size P&O (VS_PO) MPPT algorithm. The results clearly show the efficiency of the improved algorithm which contributed to the increase of the tracking speed with negligible fluctuations when the MPP is reached, and especially in rapid variation of insolation.